Attenuation of Cf-Mediated Defense Responses at Elevated Temperatures Correlates With a Decrease in Elicitor-Binding Sites - Camiel F. de Jong; Frank L. W. Takken; Xinzhong Cai; Pierre J. G. M. de Wit; Matthieu H. A. J. Joosten (Molecular Plant-Microbe Interactions, 2002)
The interaction between the fungal pathogen Cladosporium fulvum and its only host, tomato, is a well-described gene-for-gene system and several resistance (Cf) genes of tomato and matching fungal avirulence (Avr) genes have been characterized. Transgenic tobacco suspension cells expressing Cf genes respond to matching elicitors with typical defense responses, such as medium alkalization and an oxidative burst. We found that this response is attenuated at elevated ambient temperatures. Tomato seedlings expressing both a Cf and the matching Avr gene rapidly die as a result of systemic necrosis at normal temperatures, but are rescued at 33°C. We demonstrate that, at 33°C, the Cf/Avr-mediated induction of defense-related genes is reversibly suppressed. Furthermore, in cell suspensions, the AVR-induced medium alkalization response is slowly suppressed upon incubation at 33°C, but is quickly restored after transfer to lower temperatures. A high-affinity binding site (HABS) for AVR9 is present on plasma membranes isolated from solanaceous plants and has been suggested to act as a co-receptor for AVR9. The amount of AVR9-HABS is 80% reduced in tobacco cell suspensions incubated at 33°C, as compared with cell suspensions incubated at 20°C. Our data suggest that the temperature sensitivity of Cf-mediated defense responses resides at the level of perception of the fungal avirulence factors.